BALB/c-3T3 fibroblasts resistant to growth inhibition by beta interferon exhibit aberrant platelet-derived growth factor, epidermal growth factor, and fibroblast growth factor signal transduction. - Mundschau, L J (1991)
Several lines of evidence now exist to suggest an interaction between the platelet-derived growth factor (PDGF) growth-stimulatory signal transduction pathway and the beta interferon (IFN-beta) growth-inhibitory signal transduction pathway. The most direct examples are inhibition of PDGF-mediated gene induction and mitogenesis by IFN-beta and the effects of activators and inhibitors of the IFN-inducible double-stranded RNA-dependent eIF2 kinase on expression of PDGF-inducible genes. To further investigate the nature of this PDGF/IFN-beta interaction, we selected BALB/c-3T3 cells for resistance to growth inhibition by IFN-beta and analyzed the phenotypes of resulting clonal lines (called IRB cells) with respect to PDGF signal transduction. Although selected only for IFN resistance, the IRB cells were found to be defective for induction of growth-related genes c-fos, c-myc and JE in response to PDGF. This block to signal transduction was not due to loss or inactivation of PDGF receptors, as immunoprecipitation of PDGF receptors with antiphosphotyrosine antibodies showed them to be present at equal levels in the BALB/c-3T3 and IRB cells and to be autophosphorylated normally in response to PDGF. Furthermore, treatment with other peptide growth factors (PDGF-AA, fibroblast growth factor, and epidermal growth factor) also failed to induce c-fos, c-myc, or JE expression in IRB cells. All of these growth factors, however, were able to induce another early growth-related gene, Egr-1. The block to signaling was not due to a defect in inositol phosphate metabolism, as PDGF treatment induced normal calcium mobilization and phosphotidylinositol-3-kinase activation in these cells. Activation of protein kinase C by phorbol esters did induce c-fos, c-myc, and JE in IRB cells, indicating that signalling pathways distal to this enzyme remained intact. We have previously shown that IFN-inducible enzyme activities, including double-stranded RNA-dependent eIF2 kinase and 2',5'-oligoadenylate synthetase, are normal in IRB cells. The finding that the induction of multiple growth-related genes by several independent growth factors is inhibited in these IFN-resistant cells suggests that there is a second messenger common to both growth factor and IFN signaling pathways and that this messenger is defective in these cells.